Descent from a common ancestor restricts exploration of protein sequence space - Lada H. Isakova; Elizaveta Streltsova; Olga O. Bochkareva; Peter K. Vlasov; Fyodor A. Kondrashov (Proceedings of the National Academy of Sciences, 2026)
How functional protein sequences are distributed in sequence space is fundamentally important for evolutionary theory and protein design, particularly if a large diversity of protein functions are hidden in evolutionarily unexplored areas of the sequence space. However, this question is understudied in part because experimental and computational studies use extant sequences as a starting point to study sequence space. Here, we study whether extant sequences are representative of the entire functional sequence space. Across thousands of protein families from vertebrates and bacteria we calculate the dimensionality and the volume of sequence space occupied by extant homologs. We find that the observed dimensionality and volume of extant sequence space are minuscule, many orders of magnitude smaller than what we estimated using a model of protein evolution. Simulating sequence evolution we then quantify the impact of phylogeny, selection, and epistasis on restricting the evolutionary exploration of sequence space. We find that sequence evolution from a single common ancestor, or a single point of origin in sequence space, is by far the largest limiting factor that reduces the dimensionality and volume of extant sequence space. These results indicate that there are vast areas of functional sequence space that have not been explored in evolution because of the excessive restrictions on natural exploration of the protein sequence space imposed by the point of origin effect. We suggest that protein design methods that rely on extant sequences may be limited in their ability to discover truly novel functions.